2014
DOI: 10.1007/s10570-014-0500-3
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical properties for bio-based thermoset composites made from lactic acid, glycerol and viscose fibers

Abstract: Regenerated cellulose fibers were used to produce thermoset composites from a bio-based thermoset resin synthesized from lactic acid and glycerol. The resin was impregnated into the regenerated cellulose fiber and compression molded at elevated temperature to produce thermoset composites. Different fiber alignments (unidirectional and bidirectional), different reinforcement type (warpknitted and non-woven) and varying fiber loading (65, 70 and 75 wt%) were investigated. The composites were characterized by fle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 20 publications
6
13
0
Order By: Relevance
“…Our former study showed that soybean oil based thermoset nonwoven fiber composites had tensile strength between 70 and 100 MPa at 40-60 wt% fiber loading (Ramamoorthy et al 2012(Ramamoorthy et al , 2013. Tensile modulus of the composites was between 6 and 10 GPa while the Cellulose maximum elongation was about 2.1 %, which follow the results from our earlier studies (Ramamoorthy et al 2012(Ramamoorthy et al , 2013Esmaeili et al 2014). Further, acoustic emissions could be used to analyze microstructural damage analysis (Bravo et al 2015).…”
Section: Resultssupporting
confidence: 78%
See 3 more Smart Citations
“…Our former study showed that soybean oil based thermoset nonwoven fiber composites had tensile strength between 70 and 100 MPa at 40-60 wt% fiber loading (Ramamoorthy et al 2012(Ramamoorthy et al , 2013. Tensile modulus of the composites was between 6 and 10 GPa while the Cellulose maximum elongation was about 2.1 %, which follow the results from our earlier studies (Ramamoorthy et al 2012(Ramamoorthy et al , 2013Esmaeili et al 2014). Further, acoustic emissions could be used to analyze microstructural damage analysis (Bravo et al 2015).…”
Section: Resultssupporting
confidence: 78%
“…The glass transition temperature of the composites was over 100°C; higher than that of the neat resin. T g increase on addition of cellulosic fibers was due to restricted mobility of the polymer chains in the interphase and was observed previously by several authors (Å kesson et al 2011;Esmaeili et al 2014).…”
Section: Density and Porosity Measurementssupporting
confidence: 77%
See 2 more Smart Citations
“…Similar results were noticed in cellulose based composites, and the tensile properties decreased due to brittleness of thermoset matrix [9,17]. Modulus could suggest the toughness of the composites; high moduli of polymer composites in many cases indicate less tough materials [11,18]. Toughness of the composites is discussed with impact properties.…”
Section: Tensile Propertiessupporting
confidence: 65%